President's Message - McLeod, Bonnie (Operating Room Nurses Association of Canada Journal, 2010)
Many of us are creatures of habit. We prefer the comforts of the predictable to the discomforts of the strange: the route we drive to work, the stores we shop at, the parking spot we select. We tolerate change but we’d like it to be on our own terms. But, change is almost constant in the “new normal” state of life, and there is no escaping it.